Role of nitric oxide in the control of luteinizing hormone-releasing hormone release in vivo and in vitro. - Rettori, V (1993)
Nitric oxide (NO) synthase, the enzyme which converts arginine into citrulline plus NO, a highly active free radical, has been found in many neurons in the brain, including neurons in the hypothalamus. Our previous experiments showed that norepinephrine-induced prostaglandin E2 release from hypothalamic explants incubated in vitro is mediated by NO. Since the release of luteinizing hormone-releasing hormone (LHRH) is also driven by norepinephrine and prostaglandin E2, we hypothesized that NO might also control pulsatile release of LHRH in vivo, resulting in turn in pulsatile release of luteinizing hormone (LH). To ascertain the role of NO in control of pulsatile LH release in vivo, an inhibitor of NO synthase, NG-monomethyl-L-arginine (NMMA), was microinjected into the third cerebral ventricle (1 mg/5 microliters) of conscious castrate male rats at time 0 and 60 min later; blood samples were taken every 10 min during this period. NMMA blocked pulsatile LH release within 20 min, and plasma LH concentration declined further without pulses after the injection at 60 min. Pulsatile release of LH was not altered in diluent-injected controls. NMMA did not alter pulsatile release of follicle-stimulating hormone, which suggests that its release does not require NO. Incubation of medial basal hypothalami with norepinephrine (10 microM) induced an increase in LHRH release that was inhibited by NMMA (300 microM). NMMA alone did not alter basal LHRH release, whereas it was augmented by sodium nitroprusside (100 microM), which releases NO spontaneously. This augmentation was prevented by hemoglobin (2 micrograms/ml), which binds the NO released by nitroprusside. Our previous experiments showed that norepinephrine-induced release of prostaglandin E2 is mediated by NO. Nitric oxidergic neurons were visualized in the median eminence adjacent to the LHRH terminals. The combined in vivo and in vitro results indicate that the pulsatile release of LHRH induced by norepinephrine is brought about by alpha 1-adrenergic activation of NO synthase. NO then induces prostaglandin E2 release that activates exocytosis of LHRH secretory granules into the portal vessels to induce pulsatile LH release.